(The effect of using the child theater in developing some of the life skills of the children of kindergartens) (Journal of the College of Basic Education, 2019)
This research aims to develop the life skills of the children of kindergartens. The researcher used the experimental to reach the results of the research and to identify the effectiveness of the child theater (Glove Dolls) in developing some life skills (problem solving, decision making, contact with others) in kindergartens children. The researcher used the pre and post measurements for the two groups (experimental and control) to determine the effect of the independent variable on the dependent variable by applying the scale to the experimental group only. The research community was the pre-school children (4-6) years. The researcher selected the children from Al-Nargis Kindergarten in the district of Al-Khalis in Diyala. Level Two. The sample of the research was chosen from halls (1-2) deliberately. It consisted of (60) children Divided into two Groups, the experimental groups consisted of (30) male and female children and control group consisted of (30) male and female children The researcher prepared the life skills scale using the glove dolls for the children of kindergarten divided into three skills (problem solving skills 10 situations, decision-making skill 10 situations, the skill of communication with others 10 situations) and then the researcher measured the validity and stability of the scale using the Cronbach's alpha method. In the light of the research results, there are no statistically significant differences between the two groups (experimental and control) in the pre-measurement of life skills. There are statistically significant differences between the experimental and control groups in the post-measurement of life skills. The researcher reached a number of recommendations and suggestions, including the preparation of training courses for kindergarten teachers to train them on how to use the life skills in their personal lives and then train the children of kindergarten to use them successfully According to the principle (those who lack cannot given). And the need for the Ministry of Education and the media to raise awareness of the teachers and mothers who take care of children in how to train kindergarten children on the life skills due to the importance of the first ten years of the child's life on his/her personality in the future (prevention is better than treatment). The researchers suggested conducting a follow-up study on the effect of Glove Dolls use on the development of the life and social skills of primary school children and conducting a study on the aggressive behavior of kindergarten children using puppet theater.